1999
DOI: 10.1097/00006534-199911000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Limb-Sparing Surgery with Reinnervated FreeMuscle Transfer following Radical Excision of Soft-Tissue Sarcoma in the Extremity

Abstract: Limb-sparing surgery is the preferred approach in the management of patients with high-grade soft-tissue sarcomas when local disease can be completely resected. However, conventional treatment focuses only on restoration of basic functions to the remnant limb. Lost functions are not restored to normal, leaving the patient with variable degrees of functional disabilities. This in turn may necessitate further massive reconstructive procedures. Transferred reinnervated free muscles were used to reconstruct functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 5 publications
3
32
0
Order By: Relevance
“…14 The transfer of latissimus dorsi is best indicated in cases in which at least one head of the four heads of the quadriceps muscle could be spared. 29 In this study; patients in which three heads of the muscle had been resected, had considerable improvement of the function in correlation to the progressing reinnervation of the transferred muscle.…”
Section: Quadriceps Muscle Reconstruction 195mentioning
confidence: 99%
See 1 more Smart Citation
“…14 The transfer of latissimus dorsi is best indicated in cases in which at least one head of the four heads of the quadriceps muscle could be spared. 29 In this study; patients in which three heads of the muscle had been resected, had considerable improvement of the function in correlation to the progressing reinnervation of the transferred muscle.…”
Section: Quadriceps Muscle Reconstruction 195mentioning
confidence: 99%
“…The free functioning muscle transfers have many indications in both upper limb 12 and in craniofacial 13 reconstructive surgeries, although it is rarely used for the lower limb motor reconstruction. 14 Total or partial reconstruction of the quadriceps after soft tissue's sarcomas excision with free functioning latissimus dorsi muscle transfer has become more popular in the last years because of the relative efficacy of the technique in reducing functional deficits after the loss of the extensor compartment of the thigh.…”
mentioning
confidence: 99%
“…12 To avoid a decrease in leg strength and knee extension, the intraoperative linking of the vastus lateralis muscle with the vastus medialis muscle, especially in their lower third, and an extensive postoperative rehabilitation and training program are important. Doi et al 13,14 reported on two reinnervated free gracilis muscle transfers following radical excision of soft-tissue sarcoma in the lower leg. All extensor muscles of the ankle and toes were resected, and their gracilis muscles were transferred.…”
Section: Discussionmentioning
confidence: 99%
“…The motor nerve of the gracilis was sutured to the motor branch of the tibialis anterior muscle from the peroneal nerve, resulting in gradual increase in power and range of toe and ankle extension postoperatively. In a second series by Doi et al [42] , reinnervated latissimus dorsi transfer was used to improve or supplement knee flexion or extension by connecting to the sciatic or femoral nerve at the time of reconstruction.…”
Section: Nerve Reconstructionmentioning
confidence: 99%